Reimagining Musical Collaboration: AI and Music Real-Time Communication (M-RTC), The Future of Musical Creativity - Dana Kemack Goot (Journal of the Association for Technology in Music Instruction, 2025)
This project explored the intersection of Music Real-Time Communication (M-RTC), artificial intelligence (AI), and machine learning (ML) in online musical collaboration. Presented at the 2023 National CMS/ATMI conference, the project served as a preliminary inquiry into how online musicking technologies impact human-to-human interactions and sought out the capabilities in creativity in music technology. The live performance featured three musicians performing from different geographic locations using an AI-generated composition and an AI-powered accompaniment application. The project demonstrated the creative potential of integrating AI and ML into M-RTC, expanding the possibilities for remote collaboration, composition, and performance. The musicians navigated both the opportunities and limitations of the chosen technologies. Their reflections highlighted how advancements in Internet connectivity, platform design, and AI responsiveness could further optimize real-time musical collaboration. These findings contribute to discussions on the future of AI-enhanced music education, cultural exchange, and remote collaboration. As AI continues to shape educational methodologies, its thoughtful integration into M-RTC may offer more engaging and personalized learning experiences, prompting further exploration of policy and technical development.
Keywords: music; Music Real-Time Communication (M-RTC); Artificial Intelligence (AI); Machine Learning (ML); Internet; Networked Music; online musicking; music collaboration